ANALYSIS OF THE INFLUENCE OF SERVICE AND PRICING STRATEGY ON TAMAN SMART VISITOR SATISFACTION - Sulistyo, Agung (Universitas Muhammadiyah Kalimantan Timur, 2025)
This study examines and analyzes the effect of service quality and pricing strategies on visitor satisfaction at Taman Pintar Yogyakarta. This research is quantitative research. The population and sample in this study were visitors to Yogyakarta Smart Park. The sampling technique used purposive sampling and based on the Slovin formula obtained the number of respondents as many as 97 people. The data collection technique used a questionnaire distributed through the Google form and directly at Taman Pintar Yogyakarta which had been tested for validity and reliability. The analytical method used is multiple linear analysis with the SPSS 25 application tool. The results show that: (1) From the results of the multiple linear regression equation it is known that service quality and pricing strategy have a positive influence on visitor satisfaction at Taman Pintar Yogyakarta; (2) Through the F test it is known that service quality and pricing strategy simultaneously have a significant influence on visitor satisfaction at Taman Pintar Yogyakarta; (3) Through the t-test it is known that service quality partially has a positive and significant effect on visitor satisfaction at Taman Pintar Yogyakarta; (4) Through the t-test it is known that the pricing strategy partially has a positive and significant effect on visitor satisfaction at Taman Pintar Yogyakarta. (5) Through the R2 test it is known that service quality and pricing strategy contribute 57% to visitor satisfaction at Taman Pintar Yogyakarta.